2009
DOI: 10.1021/nn9014032
|View full text |Cite
|
Sign up to set email alerts
|

Polymer−Cisplatin Conjugate Nanoparticles for Acid-Responsive Drug Delivery

Abstract: We report the synthesis of novel acid-responsive therapeutic nanoparticles (NPs) with sub-100 nm size consisting of polymer-cisplatin conjugates. The uniqueness of these drug delivery polymeric NPs lies in the covalent conjugation of each cisplatin drug to the hydrophobic segment of two biocompatible diblock copolymer chains through hydrazone bond, resulting in highly differential drug release profile at different environmental acidity. We demonstrate that the synthesized polymercisplatin conjugates can readil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
262
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(267 citation statements)
references
References 29 publications
2
262
2
1
Order By: Relevance
“…That leads to a less therapeutic efficacy. To prevent this process and to increase the antitumor effect of the drug, the incorporation of cis-Pt molecules to nanosized carriers like polymers is used [13][14][15][16]. Such conjugates improved the drug pharmacokinetics and results in an increased drug accumulation in tumors, which is based on the "enhanced permeability and retention" effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That leads to a less therapeutic efficacy. To prevent this process and to increase the antitumor effect of the drug, the incorporation of cis-Pt molecules to nanosized carriers like polymers is used [13][14][15][16]. Such conjugates improved the drug pharmacokinetics and results in an increased drug accumulation in tumors, which is based on the "enhanced permeability and retention" effect.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such system can deliver simultaneously two or more drugs for the combination therapy [16,17]. It was reported that linear water-soluble polymers, block copolymers able to form micelles [13][14][15][16][17], and branched polymers have been studied as nanocarriers for chemotherapeutic agents [18]. Such nanosystems containing cis-Pt can be efficiently accumulated in the tumors, thereby enhancing the antitumor action.…”
Section: Introductionmentioning
confidence: 99%
“…The prodrug conjugate, characterized by the presence of an acid-responsive hydrazone bond, was synthesized and it was demonstrated to form NPs by self-assembly via a precipitation method [10]. These NPs showed well-controlled drugloading yield, excellent acid-responsive drug-release properties and potent cytotoxic activity against ovarian cancer [11].…”
Section: Polyethylene Glycolmentioning
confidence: 99%
“…To improve the therapeutic index of cisplatin while minimizing its adverse side effects, cisplatin analog Pt(IV) prodrugs have been synthesized. Recently the functionalization of a cisplatin analog (9) with a PEG-polylactide copolymer that was covalently bonded to the hydroxylic groups of compound 9 was reported [11]. In vitro evaluation in the A2780 human ovarian carcinoma cell line showed an approximate sevenfold cytotoxicity increase for NPs with cisplatin analog 9 and this result could be due to the burst drug release in the acidic intracellular environment.…”
Section: Page 13 Of 25mentioning
confidence: 99%
“…This prohibits the division of the cells and ultimately results in cellular apoptosis. [3][4][5] However, its clinical use is limited due to its significant toxic side effects, such as acute nephrotoxicity and chronic neurotoxicity. cis-dichlorodiammineplatinum(II) (CDDP) shows a rapid distribution over the whole body and high glomerular clearance within 15 min after intravenous injection.…”
Section: Introductionmentioning
confidence: 99%